Public Perception of Tiro Reservoir Development in Blang Rukui Village, Tiro District, Pidie Regency - Muammer Diandra; Anita Rauzana; Eldina Fatimah (Direktorat Penelitian dan Pengabdian Kepada Masyarakat, 2021)
Development and environment are two components that influence each other. The physical environment is needed as a provider of natural resources which will be further processed, while the social environment provides human resources as development actors. In the implementation of development, knowledge becomes a very important component. Because knowledge is a strong basis for consideration in generating critical thinking. Knowledge, experience, expectations, information will shape the public's perception of a phenomenon, in this case the construction of the Tiro Reservoir. One of the sub-districts that has agricultural potential that has not been managed properly is Tiro District in Pidie District. The government through the Sumatra River Basin I (BWS SI) plans to build a reservoir located in Blang Rukui Village, Tiro District, Pidie Regency. The impact of the refusal of some communities can be clearly seen in the land acquisition process that has not been carried out to date, which means that some communities do not give their land to be paid for by the government. The method in this study is to conduct direct observations to the research site by using a questionnaire to see whether the public's perception supports or does not support the construction of this reservoir. Based on the results of the questionnaire, it is known that the average public perception of the construction of the Tiro Reservoir is 62%, which is included in the criteria for being quite supportive in the construction of the reservoir. From the calculation results, the village affected by the development (village to be relocated) is Blang Rukui Village. Of the 29 samples in the village (Blang Rukui Village) affected by the construction, 25 samples did not support the construction of the reservoir and 4 samples were quite supportive. Meanwhile, in the villages (Pulo Kenari, Dayah Teungoh, Dayah Baroh, Panton Beunot) who received the benefits 47 samples supported the construction of the reservoir and the remaining 19 samples were sufficient to support the construction of the reservoir. Based on the results of calculations and discussions, it can be concluded that the results of community perceptions, although in the low category, are still quite supportive for development.